(untitled) (Eurasian Scientific Herald, 2023)
This article gives information about phraseological units in linguistics in many different languages. The primary emphasis rests on the consideration of the concepts "linguistic picture of the world", "national linguistic picture of the world" and the problem of interrelation of language and culture. Phraseological units very often reflect the peculiarities of the culture of the language they belong to; moreover they reflect history of that nation, their attitude towards world, stereotypes they believe in, etc. Furthermore, phraseological units usually are formed from national sayings, prejudices, and cultural traditions. Phraseological units represent quite a large part of linguistics. There are a lot of phraseological units in English and Uzbek languages which are not translated literally and perceived by review. In connection with various geographical conditions, historical development, political system and religion, phraseological units, used in the literary text, not always clear.